(untitled) (Biological Sciences - PJSIR, 2011)
The effects of bran roasting temperature (160-200) °C and time (5-35 min) on the yield and quality attributes of ’Ofada’ rice bran oil were studied so as to optimize the processing conditions for maximum oil yield with least deterioration of qualities. The physico-chemical parameters of oil studied included: yield, free fatty acids, peroxide value and colour, which were recorded as 14.50%, 5.80% (as oleic), 8.25 meq / kg and 1.51 abs, respectively. The optimum conditions were 200 °C roasting temperature and 15 min roasting time. With increasing the roasting temperature from 160-200 °C and the time 5-35 min, the oil yield and colour increased 11.31-14.50% and 1.51-1.58 abs, respectively, while free fatty acid and peroxide values decreased from 12.75-5.80% and 13.75-8.25 meq / kg, respectively.